Phenomenology of the quality of life of first married women in polygamous families - Shojaei , Zahra; Honarparvaran , Nazanin (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study was conducted to investigate the phenomenology of the quality of life of first married women in polygamous families. Method: The study was performed by phenomenological method. The statistical population included first married women with polygamous husbands in Shiraz. Ten first married women with bigamous husbands were selected using purposive sampling in 2020. Sampling continued until saturation, i.e. when no new data were obtained during the interview. Data were collected using a semi-structured interview. The interview questions were designed by the researcher in the form of open-ended based on the objectives and theoretical foundations. Data were analyzed based on King & Horrocks (2010) thematic analysis. Results: The results indicated that women in these families were exposed to severe personal and social vulnerabilities such as loneliness, emotional divorce, lack of family support, reduced material well-being, physical problems, feelings of inferiority, and lack of a sense of belonging due to the husband’s polygamy. Conclusion: Polygamy causes a negative psychological atmosphere and tension in the first spouse, which will lead to marital tensions and conflicts, and ultimately unhealthy living space and disruption of family order. Therefore, the process of the whole society should be directed towards a healthy and monogamous family.